Quantification of the overall contribution of gene-environment interaction for obesity-related traits - Jonathan Sulc (Nature Portfolio, 2020)
Most gene-by-environment interaction methods rely on the availability of the interacting environment. Here, the authors propose a robust maximum likelihood method for estimating the overall statistical interaction between a genetic risk score for a continuous outcome and all environmental variables.